Influence of Population, Unemployment, and Poverty on Economic Growth in South Sulawesi Province - Hidayat, Taufik; Madris, Madris; Anwar, Anas Iswanto (PT. Riset Press International, 2023)
Poverty and economic growth are important indicators of a country’s development success. To achieve development, countries strive to optimize economic growth and reduce poverty. The purpose of this study was to determine the impact of population and unemployment on poverty and economic growth in South Sulawesi. Data from South Sulawesi Central Bureau of Statistics. This study utilizes a quantitative survey using the path analysis method. The results of this study show that demographic variables have a negative and significant impact on poverty. The unemployment rate variable has no significant positive impact on poverty. Variables such as population, unemployment and poverty have a negative and significant impact on economic growth. At the same time, population and unemployment have a large impact on poverty. At the same time, population, unemployment and poverty have a significant impact on economic growth.